Influencia de la dosificación de carragenina natural sobre la eficiencia de inhibición de la corrosión del acero astm a335 grado p22 en h2so4 1,0 m a temperaturas de 25 ºc, 45 ºc y 65 ºc - Aguirre Gonzáles, Cristhian Arnold (2018)
The corrosion inhibition of ASTM A335 grade P22 steel in a 1,0 M solution of sulfuric acid (H2SO4) at different temperatures, by the mucilage of Chondracanthus chamissoi, was investigated using weight loss methods, Tafel extrapolation, modulation of electrochemical frequency and electrochemical impedance spectroscopy. Chondracanthus chamissoi mucilage acts as an optimal corrosion inhibitor of this steel corroding in a sulfuric acid solution. The average efficiencies of inhibition at 25 °C was 84,7%; 70,8% and 71,7%; at 45 °C it was 89.9%; 91,9% and 89,7%; and at 65 °C it was 97,1%; 98,4% and 96,2%, for a mucilage concentration of 2,5 g/l. Dosages of the mucilage in the range of 0,5 to 2,5 g/l only generated a slight increase in the efficiency of inhibition. The results correspond to the average obtained with the four techniques used. It was found that the inhibition efficiency and the adsorption constant increased with the increase in temperature. The standard enthalpy of adsorption was positive and the apparent activation energy decreased with the increase in mucilage concentration. All these parameters indicate that the adsorption of Chondracanthus chamissoi mucilage in ASTM A335 grade P22 steel occurs through chemical adsorption. Also, the mucilage acts as a mixed type inhibitor and the adsorption behavior of the CCC on the surface of P22 steel in a 1,0 M H2SO4 solution conforms to the Langmuir adsorption isotherm.